Student Perceptions Regarding Sex Education in Efforts to Prevent Free Sexual Behavior at SMA Negeri 1 Jambi City in 2021 - Hubaybah Hubaybah; Fitriyani Fitriyani; La Ode Reskiaddin; Fitria Eka Putri; Adelina Fitri (International Journal of Medicine and Health, 2022)
Information and communication technology that has become increasingly sophisticated makes information spread quickly without the boundaries of space and time. This is very dangerous for teenagers who are still confused about what they can and cannot do. The type of research design used is descriptive qualitative. The research subjects were 23 people, consisting of 21 students/I SMA Negeri 1 Jambi City, 1 teacher counseling guidance and 1 vice principal in the field of public relations. Data were obtained by means of Focus Group Discussion (FGD) and In-Depth Interview. Students' perception of sex education is to explain problems related to how to interact with the opposite sex, reproductive organs, intimate relationships, and juvenile delinquency. Perceptions related to the threat of not getting sex education are that they can fall into promiscuity and free sex, get pregnant out of wedlock and can get reproductive diseases. Students' perceptions regarding the benefits of getting sex education are being able to distinguish between good and bad, and being able to avoid promiscuity. Schools provide support in efforts to prevent free sex for their students by way of socialization related to sex education by counseling guidance teachers assisted by other relevant agencies and institutions. The informant's perception of the perceived barriers in obtaining sex education is that many consider sex a taboo subject and a negative thing. The activity of providing sex education at SMA Negeri 1 Jambi City is expected to be able to apply sex education as one of the materials taught to students at school. Although activities were hampered due to the pandemic, it is hoped that the school will continue to provide sex education materials in the form of online meetings or socialization from various media.